A cost-effectiveness analysis of endoscopic eradication therapy for management of dysplasia arising in patients with Barrett's oesophagus in the United Kingdom. (4th May 2019) - Pollit, Vicki; Graham, David; Leonard, Catherine; Filby, Alexandra; McMaster, Jessica; Mealing, Stuart J.; Lovat, Laurence B.; Haidry, Rehan J.
Abstract: Background and aims: Endoscopic eradication therapy (EET) is the first line approach for treating Barrett's oesophagus (BE) related neoplasia globally. The British Society of Gastroenterology (BSG) recommend EET with combined endoscopic resection (ER) for visible dysplasia followed by endoscopic ablation in patients with both low and high grade dysplasia (LGD and HGD). The aim of this study is to perform a cost-effectiveness analysis for EET for treatment of all grades of dysplasia in BE patients. Methods: A Markov cohort model with a lifetime time horizon was used to undertake a cost-effectiveness analysis. A hypothetical cohort of UK patients diagnosed with BE entered the model. Patients in the treatment arm with LGD and HGD received EET and patients with non-dysplastic BE (NDBE) received endoscopic surveillance only. In the comparator arm, patients with LGD, HGD and NDBE received endoscopic surveillance only. A UK National Health Service (NHS) perspective was adopted and the incremental cost-effectiveness ratio (ICER) was calculated. Sensitivity analysis was conducted on key input parameters. Results: EET for patients with LGD and HGD arising in BE is cost-effective compared to endoscopic surveillance alone (lifetime ICER £3006 per quality adjusted life year [QALY] gained). The results show that, as the time horizon increases, the treatment becomes more cost-effective. The 5 year financial impact to the UK NHS of introducing EET is £7.1m. Conclusions: EET for patients with low and high grade BE dysplasia, following updated guidelines from the BSG, has been shown to be cost-effective for patients with BE in the UK.